Propagation of Mouth-Generated Aerosols in a Modularly Constructed Hospital Room - Mutaz Suleiman (MDPI AG, 2021)
Modular construction methods have been widely used in the civil engineering industry due to ease of assembly, the convenience of design, and allowing for flexibility in placement while making the construction more sustainable. With the increasing number of COVID-19 cases, the capacity of the hospital is decreasing as more intensive care units (ICU) are allocated to COVID-19 cases. This limited capacity can be addressed by using modular construction to provide field hospitals. This paper adopts transient Lagrangian computational fluid dynamics simulations to investigate the importance of having an appropriate ventilation system in place to ensure sustainable infection control against airborne viruses and pathogens within a modular room. The performance of having a ventilation system using 10, 20, and 40 air changes per hour (ACH) was examined. In addition, different room configurations were also compared to provide useful guidelines for air conditioning units placement. It was determined that as the ACH rate increases while maintaining a direct flow field between the inlet and outlet, the rate of aerosol removal increases. Furthermore, the flowfield in which can be controlled by the placement of the inlet and outlet can impact the removal of aerosols, as it dictates how far the droplets travel before being removed from the enclosure.